2017
DOI: 10.3233/jad-161226
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Biomarkers of Alzheimer’s Disease as Identified in Saliva using 1H NMR-Based Metabolomics

Abstract: Using 1H NMR metabolomics, we biochemically profiled saliva samples collected from healthy-controls (n = 12), mild cognitive impairment (MCI) sufferers (n = 8), and Alzheimer's disease (AD) patients (n = 9). We accurately identified significant concentration changes in 22 metabolites in the saliva of MCI and AD patients compared to controls. This pilot study demonstrates the potential for using metabolomics and saliva for the early diagnosis of AD. Given the ease and convenience of collecting saliva, the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 24 publications
1
71
1
Order By: Relevance
“…Despite the higher sensitivity of MS-based methods, NMR enables simpler sample preparation and faster, non-destructive (i.e., samples may be recovered for subsequent analysis by other methods) and more reproducible analysis (Emwas et al, 2013;Gil & Duarte, 2018). Following on blood/urine metabolomics (Duarte, Rocha, & Gil, 2013;Pinto et al, 2016), saliva has shown promising results regarding several pathologies (Yilmaz et al, 2017;Zhang et al, 2014), including periodontal disease in adults (Barnes et al, 2011;Giannobile, 2012). In addition, metabolomics of adults' saliva has addressed intra-and inter-individual variability and the effects of gender and stimulation (Dame et al, 2015;Neyraud, Tremblay-Franco, Gregoire, Berdeaux, & Canlet, 2013;Silwood, Lynch, Claxson, & Grootveld, 2002;Takeda et al, 2009).…”
mentioning
confidence: 99%
“…Despite the higher sensitivity of MS-based methods, NMR enables simpler sample preparation and faster, non-destructive (i.e., samples may be recovered for subsequent analysis by other methods) and more reproducible analysis (Emwas et al, 2013;Gil & Duarte, 2018). Following on blood/urine metabolomics (Duarte, Rocha, & Gil, 2013;Pinto et al, 2016), saliva has shown promising results regarding several pathologies (Yilmaz et al, 2017;Zhang et al, 2014), including periodontal disease in adults (Barnes et al, 2011;Giannobile, 2012). In addition, metabolomics of adults' saliva has addressed intra-and inter-individual variability and the effects of gender and stimulation (Dame et al, 2015;Neyraud, Tremblay-Franco, Gregoire, Berdeaux, & Canlet, 2013;Silwood, Lynch, Claxson, & Grootveld, 2002;Takeda et al, 2009).…”
mentioning
confidence: 99%
“…However, further experiments with larger sample sizes and those that involve the implementation of this experimental method for the potential detection of other neurological conditions, such as MCI and Parkinson's disease, are pending. Another study successfully profiled saliva metabolites obtained from normal, MCI, and AD subjects with 1 H NMR metabolomics 75 . Although this field of research has only recently emerged, the development of reliable and sensitive salivary biomarkers would be significant as an early periodic screening tool for those susceptible to AD.…”
Section: Oral Fluidsmentioning
confidence: 99%
“…Commercial ELISA Salivary Aβ42 is significantly elevated in AD patients [72][73][74] Metabolites NMR spectroscopy There are several candidate AD biomarkers in saliva 75,92 Ocular Aβ FLES Ocular Aβ levels correlate with quantitative PET and predict AD 93 Ocular-retina…”
Section: Aβ42mentioning
confidence: 99%
“…In general related to body fluids, future studies are warranted combining proteomics, metabolomics [39] and genomic evaluations with large cohorts.…”
Section: Saliva Biomarkersmentioning
confidence: 99%